Implementation of Environmental Dispute Settlement Through Absolute Responsibility Before and After The Implementation of Omnibus Law - Peggy Dian Septi Nur Angraini; Absori (LEGAL BRIEF, 2022)
The environment has a very important role in society. Land fires are something that will have a detrimental impact. The method used is a normative juridical research method using a statutory approach, a conceptual approach, and a case approach. Then in this paper aims to determine the principle of absolute responsibility as environmental law enforcement is determined in the provisions of Article 88 of Law Number 32 of 2009 concerning Environmental Protection and Management. With the principle of responsibility that can provide justice for everyone to get the right to an environment. Then also examines the relevance of the judge's decision to environmental laws and regulations with absolute responsibility carried out by the corporation in the case of land fires in the civil decision number 107/Pdt.G/LH/2019/PN Jmb. However, then the provisions of Article 88 of Law Number 11 of 2020 concerning Job Creation eliminate the principle of absolute responsibility. The abolition of absolute responsibility in the settlement of environmental disputes is considered a shift as if it provides an opportunity for corporations to pollute the environment without absolute responsibility. Then the government seems to protect the sustainability of corporations more than the community. Keywords: Civil Decision Cases; Absolute Responsibility; Omnibus Law.